Zespół ludowy "Watra" i jego rola w upowszechnianiu kultury = Folk band WATRA and its role in the dissemination of culture - Kataryńczuk-Mania, Lidia; Poliszuk, Dorota (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents selected threads from the history and activity of the "WATRA" folk group from Brzeźnica, Lubuskie Province. The team members were interviewed to show a slice of the richness of tradition, successes and passions that convey various cultural values.
Keywords: zespół ludowy; tradycja; kultura; aktywność artystyczna; folk band; tradition; culture; artistic activity